Customizing well-known sustainability assessment tools for Iranian residential buildings using Fuzzy Analytic Hierarchy Process. (15th January 2018) - Zarghami, Esmaeil; Azemati, Hamidreza; Fatourehchi, Dorsa; Karamloo, Mohammad
Abstract: The aim of this research is to customize the categories and criteria points of well-known sustainability assessment tools regarding the priorities in sustainability concerns of Iran in order to develop an Iranian sustainability assessment tool suitable for residential buildings. Therefore, common sustainability indicators of LEED, BREEAM, CASBEE and SBTool will be used as benchmarks for the evaluation process by Iranian professional experts to revise the points allocated in Iranian assessment tool. For the revision of the points in accordance with Iranian sustainability needs, FAHP method (Fuzzy Analytical Hierarchy Process) will be conducted. Afterwards, Iranian sustainability assessment tool, consisting of six levels of certification with categories and criteria points, has been designed to promote sustainability in the residential buildings. The reliability of the assessment tool has been confirmed by comparing performance sensitivity with the existing assessment tools in terms of the points given to each category. This will encourage Iranian construction practitioners to be more aware of worldwide sustainability assessment tools and of the way to implement sustainability in their residential building projects. Results can be a basis for further investigations on other indicators which are crucial for sustainability concerns of Iran and would provide a platform for inspiration of further sustainability solutions. Introduction of the priority weights of sustainability fundamentals will be a reference for further developing a more holistic assessment tool, considering more dimensions such as economic and social sustainability issues regarding Iranian residential buildings. Highlights: Well-known international assessment tools have been customized for the context of Iran. The reliability of the proposed assessment tool was confirmed by comparing it withthe evident. Performance sensitivity of ISAT was compared to the existing international assessment tools. The fuzzy AHP method was used in order to involve quantitative approach as well as qualitative approach in the research. The tool can be used as a starting point and a profitable reference for building practitioners of developing countries.